Walking the Talk on Social Equity: A Call for Advancing the Fourth Pillar of Public Administration - Mulyadi, Asal Wahyuni Erlin; Kusumasari, Bevaola; Keban, Yeremias T. (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Once had been emphasized in the New Public Administration (Frederickson, 1990), equity is subsequently named as thefourth pillar of public administration by the National Academy of Public Administration (NAPA) in 2005, together with the other three pillars, namely Economy, Efficiency, and Effectiveness (called as the 4E’s). The pillar of equity emerged with the development of public administration reflecting the success of economic development in both developed and developing countries that still raisen justice issues. Keban (2001) stated that social equity and social justice must be fundamental principles in public administration.Subarsono (2008) and Kumorotomo (2014) also confirmed that for choosing public policy alternatives, one of the variables to consider is “able to promote equity and fairness in society” or guarantee equal resources across the country. Unfortunately, of the four pillars of public administration, the application of equity is still far behind that of the other three pillars: economy, efficiency, and effectiveness (Andrews & Van de Walle, 2012; Wang & Mastracci, 2012; Johnson-III, 2011; Charbonneau & Riccucci, 2008; Miller, Kerr, & Ritter, 2008). To precisely declare social justice as an objective of public policy is still not much of a challenge to the public administrator (Wooldridge & Gooden, 2009). This review is intended to discuss and examine the emerging issue of social equity in public administration and its application on the public policy performance measurement that has not received the same attention as the other three pillars. This is expected to provide an academic contribution to advance equity in the development of public administration particularly in Indonesia.